Kepemimpinan Blusukan: Model Kepemimpinan Kristen Yang Membumi - Yahya Usat (Integritas: Jurnal Teologi, 2019)
Leadership is generally full of rhetoric, while the life of ministry requires leadership that touches the real needs of the person being led. Therefore, the authors conducted a library research to discuss this topic. From the results of the analysis and synthesis of several literary sources by the author, the leadership that touches the real needs of the people being led is grounded leadership. The real form of leadership that is down to earth is leadership that really touches the needs of followers or subordinates through the approach of character and commendable traits where there is sincerity to serve and sacrifice for the benefit of all those who are led fairly. The grounded leadership is inherent in leaders who do not see themselves as rulers or governments that rule over people who are led arbitrarily, but servant-hearted leaders where they carry out their duties on the principle of serving and not to be served.